2017
DOI: 10.20448/journal.500/2017.4.1/500.1.57.64
|View full text |Cite
|
Sign up to set email alerts
|

Tax Incentives and the Flow of Foreign Direct Investment to Non-Oil Sector: Empirical

Abstract: Foreign Direct Investment has become an important source of bridging the gap between domestic savings and domestic investments in developing countries in the past three decades. In order to increase the flow of foreign direct investment, Nigeria like many other developing countries reformed her tax system in late 1990s to create incentives for the flow of foreign direct investment into the country. She reviewed company income tax downward from 50% in 1980s to 30% in 1999. Similarly, investment allowance was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…The results revealed that Nigeria enjoys tax incentives such as the allowance and the initial allowance in free trade zones. This is similar to the findings of Amuka and Ezeudeka (2017), who carried out a research study on tax incentives and the flow of foreign direct investment to the non-oil sector. The study looked into whether the incentive policy had made a significant difference in the pattern of foreign direct investment in the non-oil sector.…”
Section: Empirical Reviewsupporting
confidence: 87%
“…The results revealed that Nigeria enjoys tax incentives such as the allowance and the initial allowance in free trade zones. This is similar to the findings of Amuka and Ezeudeka (2017), who carried out a research study on tax incentives and the flow of foreign direct investment to the non-oil sector. The study looked into whether the incentive policy had made a significant difference in the pattern of foreign direct investment in the non-oil sector.…”
Section: Empirical Reviewsupporting
confidence: 87%
“…Variants of studies have been conducted to investigate the impact of tax incentives on the pattern of FDI inflows in Nigeria. Interestingly, while the findings of most of those studies tend to be similar and that is that tax policy and incentives have a significantly positive effect on FDI (Amuka & Ezeudeka, 2017;Effiok et al, 2013;Olaniyi, Ajayi, & Oyedokun, 2018;Ugwu, 2018). Other studies found out the contrary (Peters & Kiabel, 2015;Saidu, 2015;Sheedy, Zhang, & Tam, 2017).…”
Section: Background Issuesmentioning
confidence: 90%
“…Unfriendly tax policy or relatively higher tax costs diminish profit which overtime may probably affect the motivation for foreign investment. Amuka and Ezeudeka (2017) asserted that the recent aggressive use of tax incentives in attracting FDI is borne out of the notion that a favourable tax policy will have a positive effect on the flow of FDI into a country.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…They found that the response of FDI to tax is negatively significant which aligns with the findings of (Saidu, 2015). Amuka and Ezeudeka (2017) studied the effect of taxes and the flow of FDI to non-oil sector. The study used company income tax as the only tax variable and produced similar results to those of (Babatunde & Adepeju, 2012: Saidu, 2015.…”
Section: Literature Reviewmentioning
confidence: 99%